Description of the State of the Polytheists in Surat Al-An’am - an Objective Study - (Islamic Sciences Journal, 2023)
ABSTRACT                         The name Al-An’am was given to this surah because of the verses that were mentioned in it that talk about livestock, and it is the first Meccan surah in the order of the Qur’an. The number of its verses is 165 verses, it was revealed at the beginning of the Islamic call, and from the merits of this surah is that it is the first surah that was revealed to the heart of the Messenger, may God bless him and grant him peace, all at once. At once, seventy thousand angels spread it, and this surah can be called the surah al-Tawhid or the surah of the beliefs of Islam, as it is the first pillar of the Islamic faith and from it the scholars extracted the rules of monotheism and the principles of religion. The surah dealt with important issues in the principles of faith, namely the issue of divinity, mission, resurrection, and recompense. It included two important methods, namely, the method of teaching the Messenger, may Allah’s prayers and peace be upon him, the argument to argue with the polytheists, and the method of reporting by presenting evidence related to monotheism and evidence of Allah’s power. The surah gradually dealt with issues, beginning with how the universe came into being and the stages of its creation , and confronted the infidels who were suspicious of Allah Almighty, and concluded by revealing the mission of man on this earth, which is the succession of the earth and its reconstruction.